Emotions are not always contagious: Longitudinal spreading of self-pride and group pride in homogeneous and status-differentiated groups. Issue 1 (2nd January 2016) - Delvaux, Ellen; Meeussen, Loes; Mesquita, Batja
Abstract : The members of task groups are emotionally more similar to each other than to others outside the group; yet, little is known about the conditions under which this emotional similarity emerges. In two longitudinal studies, we tested the idea that emotions only spread when they contain information that is relevant to all group members. We compared the spreading of group pride (relevant) with self-pride (not relevant). The first study followed emotions in 68 task groups ( N = 295) across 4 moments. Multilevel cross-lagged path analyses showed that group members mutually influenced each other's group pride, but not self-pride. The second study followed emotions in 27 task groups ( N = 195) across 3 moments in time. Longitudinal social network analyses showed that group members adjusted their group pride, but not their self-pride, to members they perceived to be more influential. Findings from both studies are consistent with a social referencing account of emotion spreading.